Season of Birth and Marital Outcomes - Sonia Oreffice (Institute for the Study of Labor (IZA), 2014)
This study analyzes the marriage-market aspects of season of birth in the United States, estimating whether and how marital status is related to quarter of birth by gender and race, also incorporating cohabitation as a separate relationship status. For couples, additional analysis considers who is matched with whom and the spousal (partner's) trade-offs of quarters of birth and socioeconomic attributes. Using the American Community Survey data 2010-2012, I show that white women born in the fourth quarter are more likely to be married than never married (marriage more likely than cohabitation), while never married white men from the second birth quarter are less likely to be cohabiting than single. Black men from the first birth quarter are less likely to be married rather than cohabiting but more likely to be cohabiting than single. White women from the third birth quarter and black women from the second are more likely to be divorced, always controlling for demographic and socioeconomic characteristics. Among white married couples, men born in the first quarter have more educated and richer wives, and conversely women from the same first quarter have less educated husbands. In cohabiting couples, white men and women born in the third quarter have richer and less educated partners, respectively, and black women from the first quarter have poorer partners. Finally, in all types of couples, black women born in the fourth quarter have richer husbands.
Keywords: D1; J1; 330; quarter of birth; marriage; cohabitation; divorce; single; marriage market